Association between CXCL9/10 polymorphisms and acute rejection of liver allograft. Issue 8 (February 2019) - Ostojic, Ana; Markotic, Antonio; Kelava, Tomislav; Mrzljak, Anna
Abstract : Abstract: While increased serum concentrations of CXCL9/10 are associated with acute cellular rejection (ACR) occurrence, the association between CXCL9/10 single nucleotide polymorphisms (SNPs) and ACR after liver transplantation (LT) remains unknown. In the present case-control study, polymorphisms of CXCL9 (rs10336) and CXCL10 (rs3921) were determined by polymerase chain reaction in 215 liver transplant recipients. ACR was defined as biopsy proven within 6 months after LT. As selected SNPs were in 3'-UTR region, their possible association with protein synthesis was assessed by measuring the plasma concentration of CXCL9/10 in a cohort of 40 new transplant patients using ELISA. There was no association between CXCL9/10 genotypes and overall incidence of ACR. However, patients with CXCL9 genotype AA developed ACR earlier than patients with GG genotype ( P  = .003), with similar results for CXCL10 gene (CC vs GG; P  = .005). There was no statistically significant difference in plasma concentrations of CXCL9/10 between the rejectors and the non-rejectors. Of note, patients with AA CXCL9 genotype had significantly higher CXCL9 plasma concentrations than patients with AG ( P  = .01) or GG genotype ( P  = .045). In conclusion, the SNPs of CXCL9 (rs10336) and CXCL10 (rs3921) are not associated with the incidence of ACR. However, patients with CXCL9 genotype AA developed ACR earlier and the same genotype was associated with greater plasma concentrations suggesting the involvement of CXCL9 mediated processes in ACR development. Abstract : Supplemental Digital Content is available in the text